Är förekomst av knäckesjuka i tallföryngringar mindre på stora naturvårdsaspar än på aspsly? - Löfstrand, Maja (SLU/Dept. of Forest Ecology and Management, 2009)
Pine twisting rust (Melampsora pinitorqua) is a parasitic rust fungus found all across Sweden causing damage resulting in lower quality and reduced tree growth in pine stands. In Sweden, the fungus is dependent on two alternate hosts; European aspen (Populus tremula) and Scots pine (Pinus sylvestris). Pine twisting rust has five different spore stages, two of them (uredinio- and teliospores) on the leaves of aspen. Injures on aspen caused by pine twisting rust is not extensive. On the other hand, when it infects the annual shoots of Scots pine it often results in a bent steam or even a top shoot breakage. Aspens provide an essential environment for a lot of different plants and animals. Therefore, the forestry of today often retains mature aspens in pine regenerations for conservation purposes. The aim of this study was to evaluate if leaves on young aspens sprouts contain more spores of pine twisting rust than leaves on mature aspens and therefore in higher extent might spread the disease. The field study was conducted in the county of Västerbotten, during the autumn 2008, in nine infected pine regenerations with retained mature aspen and young aspens sprout. Proportion of infected leaves and coverage of spores in the tree tops was estimated by using a telescope of highest quality. For each mature aspen, leaves from four different heights, in total 100 leaves per aspen, were studied. For comparison, spore occurrence and coverage of 100 leaves on the surrounding aspen suckers (r = 10m) was estimated. In total, 41 mature aspens were included in the study. To evaluate whether infected leaves falls from the trees earlier, a pilot study was conducted at one site. Additionally, a short questionnaire was sent to forest organizations to investigate how forest owners’ look at pine twisting rust. The result of the study showed that the occurrence of spores was three times higher, and the coverage of spores, five times higher, on aspen sprouts than on mature aspens. There was no significant difference in spore occurrence in aspens tops. There were a few infected leaves even at 25-30 m height. The results indicate that mature aspen are less important compared to aspen sprouts for the spread of pine twisting rust. Thus, management practices in Scots pine regeneration should incorporate control of the more infected aspen suckers. It could also be wise to avoid planting Scots pine on fertile sites were frequency of aspen often is high.